Automated IV Infusion Control System Design and Development for Medical Use (Pakistan Journal of Scientific Research, 2023)
For patients suffering from pathological conditions, Intravenous infusion serves to be the go-to treatment, it requires for a medical practitioner to set up the IV infusion device up as per the doctors’ instructions, followed by periodic supervision as abnormalities may occur. The objective of this paper is to demonstrate the construction of an automated intravenous infusion control system. Medical and laboratory fluid control has previously been achieved using pressure-based flow sensing, ultrasonic flow measurement, optical flow sensors, capacitive flow sensing, and thermal flow sensing. Due to its reduced susceptibility to external factors, our approach utilizing an IR sensor is particularly advantageous in IV scenarios for accurately detecting fluid drops. An IR sensor, microcontroller, servo motor/peristaltic pump, and an affordable microcontroller are used in this system to allow precise saline circulation rate control. An input control system can be implemented through either a matrix keypad or a single control network server. Controls the drops per minute and allows internet-based server-side control via IR sensor, 3x4 matrix keypad, and Bluetooth module. To accurately measure the saline flow rate and count drops, an IR sensor is integrated into the drip chamber of the saline container. In order to achieve the desired blood flow rate, the microcontroller continuously compares the sensor readings with the commands and adjusts the servo motor/peristaltic pump accordingly. Testing of the completed hardware provided satisfactory results, proving the device's ability to enhance patient care.